A case study of acoustic intervention in classrooms. Issue 4 (December 2021) - Abraham, Ajish K; Ravishankar, M S
High reverberation times (RTs) have always been an acoustic barrier to effective learning in classrooms. Acoustic corrections to reduce RT involve complex acoustic treatment. Previous studies have indicated that classrooms in most schools do not meet the established acoustic criteria, as the school authorities refrain from such acoustic treatment. Aim of the study was to optimize the RT within classrooms through easily-implementable acoustic corrections. Different combinations of acoustic corrections have been experimented in eight classrooms, through a step-by-step approach to optimize RT. After each acoustic modification, the RT was measured and the speech clarity parameter C50, was estimated. At the final step, RT of the classrooms was diminished to a mean value of 0.74 s (standard deviation = 0.04) from the initial mean value of 4.37 s (standard deviation = 0.42). C50 values corresponding to the final acoustic correction were found to fall within good speech intelligibility scale.